Estudo da camada limite interna térmica em condições de brisa do mar, utilizando diferentes parametrizações: Aplicação do modelo wrf na região da grande vitória - Salvador, Nadir; Loriato, Ayres G.; Santiago, Alexandre; Albuquerque, Taciana T. A.; Reis, Neyval C.; Santos, Jane M.; Landulfo, Eduardo; Moreira, Gregori; Lopes, Fábio; Held, Gerhard; Moreira, Davidson M. (FapUNIFESP (SciELO), 2016)
In the present study, the physical parameterizations of the Weather Research and Forecasting (WRF) model are verified for making accurate inferences about the dynamics of the Thermal Internal Boundary Layer (TIBL) generated by sea breeze in an urban center with an island in a bay along a coastal region with rugged topography. The simulations were performed using parameterizations from Yonsei University (YSU), Mellor-Yamada-Janjic (MYJ) and Asymmetric Convective Model version 2 (ACM2) for the atmospheric boundary layer (ABL) and Noah and Rapid Update Cycle (RUC) for the Land Surface Model (LSM). The data inferred by the WRF model were compared with those obtained by a Surface Meteorological Station (SMS) and by measurements generated using Light Detection and Ranging (LIDAR), Sonic Detection and Ranging (SODAR) and radiosonde. The simulations showed that although the object of this research was a region with high geographical complexity, the YSU parameterization set (non-local closure) for the ABL and the Noah parameterization for the LSM presented satisfactory results in determining ABL height generated by the sea breeze on the day in question.
Study of the thermal internal boundary layer in sea breeze conditions using different parameterizations: Application of the WRF model in the greater Vitória region
Keywords: LIDAR; Parameterization; Sea breeze; SODAR; Thermal internal boundary layer; WRF